Helminths of the mallard Anas platyrhynchos Linnaeus, 1758 from Austria, with emphasis on the morphological variability of Polymorphus minutus Goeze, 1782. (19th March 2021) - Jirsa, F.; Reier, S.; Smales, L.
Abstract: The mallard Anas platyrhynchos is the most abundant water bird species in Austria, but there is no record of its helminth community. Therefore, this work aimed to close that gap by recording and analysing the parasite community of a large number of birds from Austria for the first time. A total of 60 specimens shot by hunters in autumn were examined for intestinal parasites. The following taxa were recovered (prevalence given in parentheses): Cestoda: Diorchis sp. (31.7%) and Fimbriarioides intermedia (1.7%); Acanthocephala: Filicollis anatis (5%), Polymorphus minutus (30%) and one cystacanth unidentified (1.7%); Trematoda: Apatemon gracilis (3.3%), Echinostoma grandis (6.7%), Echinostoma revolutum (6.7%) and Notocotylus attenuatus (23.3%); Nematoda: Porrocaecum crassum (1.7%) and one not identified (1.7%). The frequency distribution of parasites showed a typical pattern in which 39 birds (65%) were either not parasitized or were harbouring up to five worms, whereas more intense infestations occurred in a lesser number of hosts. Compared to other studies from central and eastern Europe, an extremely depauperate helminth community, particularly of the cestodes and nematodes, was found. Polymorphus minutus was observed as having highly variable morphology and, therefore, molecular genetic characterization by DNA barcoding was carried out. Species identification was confirmed by comparing data with the reference cytochrome c oxidase subunit 1 gene sequence from P . minutus available in GenBank.